THE The Use of Attitudinal Domain in The English Version of Wedding Procession Natoni at South Central Timor - Faot, Yusanti Nenci; Fitriati, Sri Wuli; Faridi, Abdurrachman (English Education Journal, 2019)
This research investigated the attitudinal domain in the English version of wedding procession Natoni. The language of evaluation: Appraisal in English by Martin and White (2005) book was used as a foundation in this research. The data which consisted of photos documentation were analyzed by the researcher. The unit of analysis of this research was words or phrases in the English version of wedding procession Natoni. There were several procedures for analyzing data including reading, identifying, categorizing, and analyzing. In order to validate the findings, the data, and analysis of this research had been examined and judged by researchers. Two of them were from Universitas Negeri Semarang who previously conducted the Appraisal system research and a lecture of UKAW Kupang as an expert who has previously conducted some research related to appraisal system. The findings revealed that the appreciation was the highest appraising used in the wedding process. The use of appreciation in appraising subsystem made a man and woman able to give advice to each other in a successful wedding procession which can be seen through words or phrases they used. In conclusion, this research suggested that speakers should use the appropriate words or phrases in order to avoid misunderstanding in giving advice. In addition, by understanding the attitudinal domain, people can create a good conversation to interact with each other.